THE MANIFESTATION OF RELIGIOUS AND POLITICAL RELATIONS IN THE KISWAHILI RELIGIOUS NEWSPAPERS DURING 2015 ELECTIONS - Lugome, Faraja Kristomus (UC Journal: ELT, Linguistics and Literature Journal, 2022)
There has been a constant power struggle and unstable religious relations between Christians and Muslims in Tanzania, especially during elections. Many scholars have approached the issue of interreligious relations from the political and social dimensions, and no critical analysis on the role of religious newspapers in exacerbating such struggle and relations. This article analyzes the stories related to religious and political relations in Tanzania as religious newspapers framed them in 2015. The study used data from four selected religious newspapers published from January to December 2015 and used data from interviews and Focus Group Discussions (FGD). The selected headlines were analysed using three dimensions of Textually Oriented Discourse Analysis (TODA) propounded by Norman Fairclough. The study found that the framing of election stories was affected by the religious biases of the newspapers. The analysis further shows that the religious newspapers in 2015 presented the mistrust between Christians and Muslims. It was found that Muslims mobilised fellow Muslims to change the Christian-dominated Government because Muslims' interests have been ignored for many years. The article concludes that when the inequality grows and is left unaddressed, it leads to social unrest.